Which nutritional prognosis is better? comparison of the three most commonly performed bariatric surgeries: A systematic review and network meta-analysis - Cui, Yuanyao; Zhang, Di; Wang, Li; Liu, Xuefei; Wang, Chunyan; Tian, Shuyun; Li, Meiqu (Frontiers in Surgery, 2023)
(1) Background: Obesity is one of the most important public health conditions in the world, and surgical intervention is the only medical treatment recognized by the medical community as a complete and permanent cure for morbid obesity and its complications. The choice of surgical modality is also based more on the experience of the physician or the requirements of people with obesity, rather than on scientific data. In this issue, a thorough comparison of the nutritional deficiencies caused by the three most commonly used surgical modalities is needed. (2) Objectives: We aimed to use the network meta-analysis to compare the nutritional deficiencies caused by the three most common BS procedures in many subjects who underwent BS to help physicians determine the best BS surgical approach to apply to their clinical people with obesity. (3) Setting: A systematic review and network meta-analysis of world literature. (4) Methods: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, systematically reviewed the literature, and conducted a network meta-analysis using R Studio. (5) Results: For the four vitamins calcium, vitamin B12, iron and vitamin D, the micronutrient deficiency caused by RYGB is the most serious. (6) Conclusions: RYGB causes slightly higher nutritional deficiencies in Bariatric surgery, but RYGB remains the most commonly used modality for Bariatric surgery.